Oxidative stress and macrophage function: a failure to resolve the inflammatory response. (20th March 2007) - Kirkham, P.
Abstract : The suppression of pro-inflammatory gene expression along with the clearance of apoptotic cells by phagocytosis can play an important role in resolving the inflammatory response. Any impairment of these processes can therefore lead to a chronic inflammatory state. Oxidative stress can have both direct and indirect effects on macrophage function. This mini-review highlights a mechanism through which oxidative stress via the production of reactive carbonyls alters the ECM (extracellular matrix) environment of macrophages, thereby altering their behaviour. Carbonyl modification of ECM proteins causes increased macrophage adhesion and activation through receptors that are also involved in phagocytosis. Moreover, interaction of macrophages with these carbonyl-modified ECM proteins leads to decreased phagocytic activity towards apoptotic cells. At a more direct level, both oxidative and carbonyl stress inhibits activity of the transcriptional co-repressor HDAC-2 (histone deacetylase 2), which under normoxic conditions helps to suppress pro-inflammatory gene expression. Consequently, macrophages activated under conditions of oxidative or carbonyl stress can lead to a more enhanced inflammatory response. Coupled with an impairment of the phagocytic response, this can lead to ineffective clearance of apoptotic cells and secondary necrosis, with the result being failure to resolve the inflammatory response and the establishment of a chronic inflammatory state.